Improving Nutritional Awareness Through Food Label Reading Education among School-Age Children - Joan Herly Herwawan; Fandro Armando Tasijawa; Lea Mediatrix Y Janwarin; Hery Jotlely; Maria Nindatu (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
The nutritional status of school-age children is a crucial determinant of their health, growth, and academic performance. However, low nutrition literacy and frequent consumption of packaged foods high in sugar, salt, and fat pose significant challenges. This community service program aimed to improve students’ nutritional awareness through food label reading education at SD YPPK Waenibe (YPPK Waenibe Elementary School). The program employed health education sessions on balanced nutrition and interactive practice in reading food labels, including demonstrations of sugar and salt content. Evaluation was conducted using pre-test and post-test assessments among 19 students. Results showed a significant improvement in knowledge, with the mean score increasing from 68.37 (pre-test) to 80.11 (post-test). Most students shifted from the “fair” to the “good” knowledge category. These findings confirm that simple, practice-based educational interventions can effectively enhance nutrition literacy among school-age children. Moreover, the program has the potential to empower students as change agents in both school and family contexts. Nevertheless, this initiative was limited to a single intervention and lacked parental involvement. It is recommended that future programs be integrated into school curricula and involve parents to strengthen children’s healthy consumption behaviors.